MEKANISME KINERJA GURU MATA PELAJARAN BAHASA INDONESIA UNTUK MENCAPAI PEMBELAJARAN YANG OPTIMAL DI MADRASAH ALIYAH NEGERI SE KOTA PALU - Aniati Aniati; Rahmadini Warastuti (ISTIQRA, 2014)
This study was conducted to obtain an objective description of the mechanism of Indonesian language teachers to reach learning achievement optimally at Madrasah Aliyah in Palu. This study used descriptive qualitative approach to collect the data through observation, interviews, questionnaires and documentation and to analysis the data. The study indicated that the mechanism of Indonesian language teacher performance are that the teachers have (1) Prepared learning programs in accordance with the calendar in school education, (2) Made preparations to teach with reference to the approved curriculum in schools, (3) Made a list of student scores reported to the principal. The efforts of Indonesian language teachers to reach learning achievement optimally are that the teachers (1) Motivated their students to increase their inner motivation, (2) Prepared learning content that can stimulate the creativity of students' creativity, (3) Used the media or learning aids, (4) More emphases on the role and participation of students, and (5) Established two-way communication. Factors supporting the efforts of the teachers are (1) A curriculum that is accordance with the competence of students, (2) The method used in a variety of learning, (3) Students' high motivation and interest in learning. Keywords: Performance Mechanism, Indonesian language teachers, Learning achivement